Pemberian Edukasi Tentang Relaksasi Autogenik Dalam Menurunkan Tingkat Kecemasan Ibu Nifas di Puskesmas Putri Ayu Kota Jambi - Iksaruddin Iksaruddin; Herinawati Herinawati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
During the puerperium, mothers experience physical and physiological changes which also result in some psychological changes. The COVID-19 pandemic condition that requires the implementation of social distancing policies results in the risk of psychological responses such as stress, anxiety, and even depression in postpartum mothers. This study aims to analyze the effectiveness of providing education about autogenic relaxation in reducing the anxiety level of postpartum mothers at Putri Ayu Health Center, Jambi City. This type of research is a quasi-experimental design using a one-group pre-test-post-test design involving 32 postpartum mothers as participants at the Putri Ayu Health Center, Jambi City. Data analysis used the Wilcoxon test with an alpha limit of the significance of 0.05. The results showed that the p-value (0.0001) < 0.05, then Ho was rejected, Ha was accepted, which means that there is an effect of giving Autogenic Relaxation on the anxiety level of postpartum mothers. There needs to be socialization and education about autogenic relaxation during pregnancy to prevent as early as possible the occurrence of anxiety in the postpartum period.